Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.cell.2015.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Cell Induction by Adhesion of Microbes to Intestinal Epithelial Cells

Abstract: SUMMARY Intestinal Th17 cells are induced and accumulate in response to colonization with a subgroup of intestinal microbes such as segmented filamentous bacteria (SFB) and certain extracellular pathogens. Here, we show that adhesion of microbes to intestinal epithelial cells (ECs) is a critical cue for Th17 induction. Upon monocolonization of germ-free mice or rats with SFB indigenous to mice (M-SFB) or rats (R-SFB), M-SFB and R-SFB showed host-specific adhesion to small intestinal ECs, accompanied by host-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
779
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 875 publications
(855 citation statements)
references
References 37 publications
(45 reference statements)
28
779
0
3
Order By: Relevance
“…However, many of these studies relied on easily accessible fecal samples obtained on a single occasion, which may not properly represent mucosa-associated bacterial populations [17,18]. The mucosa-associated microbiota is considered to affect epithelial and mucosal function to a greater degree than luminal bacteria and to contribute more significantly to the pathogenesis of IBD [13,17,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these studies relied on easily accessible fecal samples obtained on a single occasion, which may not properly represent mucosa-associated bacterial populations [17,18]. The mucosa-associated microbiota is considered to affect epithelial and mucosal function to a greater degree than luminal bacteria and to contribute more significantly to the pathogenesis of IBD [13,17,32].…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies also showed that IL-17D increased human NK cell cytotoxic functions in vitro and induced MCP-1 production in tumor endothelial cells to recruit NK cells for tumor rejection in vivo. 74 Moreover, the intestinal Th17 responses against Citrobacter rodentium required a physical interaction between the intestinal epithelial cells and the microbes, 75 indicating that both the recognition of MAMP molecules and the location of the microbes are critical for the generation of proper adaptive immune responses. Candida species are fungal species that frequently colonize the oral, intestinal, and vaginal surfaces and the skin of healthy individuals.…”
Section: Il-17dmentioning
confidence: 99%
“…Similarly, a single bacterial strain, segmented filamentous bacteria (SFB), is sufficient to drive the accumulation of Th17 cells in the small-intestinal lamina propria (SI-LP) of mice (9,10); however, Th17-inducing microbes derived from the human gut have not yet been identified. A recent report did document an increase in colonic Th17 cells in GF mice inoculated with fecal material from healthy people and patients with ulcerative colitis, thus showing the existence of Th17-inducing species in the human microbiota (11). However, the microbiota composition differs substantially across both healthy individuals and colitis patients, and the symbionts responsible for Th17 cell induction at steady state remain uncharacterized (11).…”
mentioning
confidence: 99%
“…A recent report did document an increase in colonic Th17 cells in GF mice inoculated with fecal material from healthy people and patients with ulcerative colitis, thus showing the existence of Th17-inducing species in the human microbiota (11). However, the microbiota composition differs substantially across both healthy individuals and colitis patients, and the symbionts responsible for Th17 cell induction at steady state remain uncharacterized (11).…”
mentioning
confidence: 99%